Morphological and DNA Barcoding Evidence for Invasive Pest Thrips, Thrips parvispinus (Thripidae: Thysanoptera), Newly Recorded From India. Issue 1 (21st July 2015) - Tyagi, Kaomud; Kumar, Vikas; Singha, Devkant; Chakraborty, Rajasree
Abstract : South East Asia pest thrips species, Thrips parvispinus (Karny), is a serious pest on a number of agricultural and horticultural crops in a number of plant families. Based on an integrated approach of morphology and DNA barcoding, invasion of this serious pest is reported first time from India on papaya plantations. Molecular data have corroborated with the morphological identification. Haplotyping data suggested that the Indonesia may be a probable source of invasion of this pest to India.